Contemporary environment, positivism and the ordinary judge (Revista do Tribunal Regional Federal da 3ª Região, 2013)
Contemporary reality is marked by a globalized environment, subject to intense changes and surrounded by uncertainties, aspects that are also reflected in the high number of lawsuits whose disputes show great diversity accentuated by the continental dimensions of Brazilian territory. Turning our eyes to the abundant normative texts and doctrinal constructions that can illuminate the path to the solution of judicialized disputes, ordinary judges are often faced with normative precepts of high abstraction under which they transcend historical appeals demanding that jurisdictional activity be constructive and promote social justice. The aim of this study is to demonstrate some of the reasons why, intuitively or in a way that is consistently based on legal theories, ordinary Brazilian judges are moving towards a stance that uses the openness of the legal system to make legal positivism more flexible,  providing jurisdiction based on the normative element but also under the influence of moral values and socio-economic aspects of the societies to which the judicial provision is directed, with some of the virtues and risks inherent in this attitude. For the development of this study, we will initially analyze the sociological framework of the contemporary environment (with the global risk society and liquid modernity), and then we look at the legislative framework, which shows a crisis in the process of producing norms by Parliament, leading to an increase in the degree of abstraction of normative precepts, and then we analyze the historical framework that leads to the flexibilization of positivism in favor of the search for material justice in judicial activity. This flexibilization finds receptivity in the profile of the ordinary Brazilian judge, which will lead us to the conclusion that there is a need to establish control parameters for this active task of the magistrates in order to avoid excesses.
Keywords: positivism; global risk society; liquid modernity; crisis of the legislature; ordinary judge; excesses and the need for control